Characteristics of the cerebrospinal fluid pressure waveform and craniospinal compliance in idiopathic intracranial hypertension subjects - Okon, Monica D.; Roberts, Cynthia J.; Mahmoud, Ashraf M.; Springer, Andrew N.; Small, Robert H.; McGregor, John M.; Katz, Steven E. (Fluids and barriers of the CNS, 2018)
Background Idiopathic intracranial hypertension (IIH) is a condition of abnormally high intracranial pressure with an unknown etiology. The objective of this study is to characterize craniospinal compliance and measure the cerebrospinal fluid (CSF) pressure waveform as CSF is passively drained during a diagnostic and therapeutic lumbar puncture (LP) in IIH. Methods Eighteen subjects who met the Modified Dandy Criteria, including papilledema and visual field loss, received an ultrasound guided LP where CSF pressure (CSFP) was recorded at each increment of CSF removal. Joinpoint regression models were used to calculate compliance from CSF pressure and the corresponding volume removed at each increment for each subject. Twelve subjects had their CSFP waveform recorded with an electronic transducer. Body mass index, mean CSFP, and cerebral perfusion pressure (CPP) were also calculated. T-tests were used to compare measurements, and correlations were performed between parameters. Results Cerebrospinal fluid pressure, CSFP pulse amplitude (CPA), and CPP were found to be significantly different (p < 0.05) before and after the LP. CSFP and CPA decreased after the LP, while CPP increased. The craniospinal compliance significantly increased (p < 0.05) post-LP. CPA and CSFP were significantly positively correlated. Conclusions Both low craniospinal compliance (at high CSFP) and high craniospinal compliance (at low CSFP) regions were determined. The CSFP waveform morphology in IIH was characterized and CPA was found to be positively correlated to the magnitude of CSFP. Future studies will investigate how craniospinal compliance may correlate to symptoms and/or response to therapy in IIH subjects.